2003
DOI: 10.1111/1540-627x.00065
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Dispositions and Goal Orientations: A Comparative Exploration of United States and Russian Entrepreneurs

Abstract: We refine and extend the study of entrepreneurial dispositions by linking three classic hallmarks of the entrepreneur—achievement motivation, risk–taking propensity, and preference for innovation—to the goal orientations of United States and Russian entrepreneurs. The results suggest that entrepreneurial dispositions vary according to culture and the entrepreneur's primary goal for the venture. The results have important implications for theoretical development linking dispositions and entrepreneurial behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 43 publications
2
104
1
5
Order By: Relevance
“…12;2015 157 self-confidence and poverty in an alternative to the feminist approach (Snyder, 1995;Blau & Kahn, 2007). In the 2000s, research has been conducted on issues related to professional characteristics, motherhood, family position, human capital, and social entrepreneurship (Steward et al, 2003;William, 2004).…”
Section: Characteristics Of Woman Entrepreneursmentioning
confidence: 99%
“…12;2015 157 self-confidence and poverty in an alternative to the feminist approach (Snyder, 1995;Blau & Kahn, 2007). In the 2000s, research has been conducted on issues related to professional characteristics, motherhood, family position, human capital, and social entrepreneurship (Steward et al, 2003;William, 2004).…”
Section: Characteristics Of Woman Entrepreneursmentioning
confidence: 99%
“…In addition to women entrepreneurs' professional characteristics and achievements, research has been conducted on issues related to health, motherhood, family position and life style satisfaction (see Schindehutte et al, 2003;Williams, 2004, among others). Increased attention has also been paid to entrepreneurial teams and networks (see Aldrich et al, 2002;Greve and Salaff, 2003, among others), and to the study of femaleowned businesses, covering subjects such as growth and performance, management style, financing, human capital, labour markets and social entrepreneurship, among others (see Bird and Brush, 2002;Burke, 2002;Carter, 2003;Stewart et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this study has identified a number of typical indicators to represent product sustainability as a basis for materials selection, based upon the basic principles and guidelines of sustainable design to construct a decision matrix, shown in Table 1 [2,24,55,56]. For any manufacturer, there are triple bottom lines (TBL) to run a sustainable business from bottom to top, i.e., as basic market demand, alternative materials and energy for production, and pursuing societal value for environmental protection [57][58][59][60][61][62]. The manufacturer is primarily driven by profit, as economic issues play a dominant role in business operations [61,[63][64][65].…”
Section: Integrated Madm Approach For Materials Selectionmentioning
confidence: 99%